Inorganic Micelles: Inorganic Micelles (Hydrophilic Core@Amphiprotic Shell) for Multiple Applications (Adv. Funct. Mater. 38/2015). (8th October 2015) - Islam, Md. Shahinul; Choi, Won San; Kim, Sun Ha; Han, Oc Hee; Lee, Ha‐Jin
Abstract : W. S. Choi, H.‐J. Lee and co‐workers present superhydrophobic hollow SiO2 micelles (SHSMs) with hydrophilic cores and amphiprotic (superhydrophobic/hydrophilic) shells on page 6061. The unique amphiprotic functionality makes the SHSMs suitable as smart nanomaterials for multiple applications, such as amphiprotic catalytic reactions in aqueous or organic solutions, oil/water separation and pollutant purification, and enzyme immobilization, with great stability and efficient recyclability.